Cost-effectiveness analysis of implementing a field hospital in a soccer stadium during a pandemic - Bernardez-Pereira, Sabrina; Schettino, Guilherme de Paula Pinto; Marra, Alexandre R.; Parreira, Kaue Capellato Junqueira; Racy, Fabio de Castro Jorge; Miranda, Rose Mara; Codeço, Artur Martins; Jaures, Michele; Pagliuso, João Gabriel Dias; Neto, Miguel Cendoroglo; Laselva, Claudia Regina; Klajner, Sidney; et al. (Frontiers in Public Health, 2025)
IntroductionField hospitals, following the Fangcang Shelter Hospital model, were critical during the global COVID-19 pandemic to alleviate the strain on overwhelmed healthcare systems. Despite their widespread adoption, concerns persist regarding their efficacy and cost-effectiveness. This study aimed to assess the impact of the Pacaembu Field Hospital in São Paulo, Brazil during the COVID-19 pandemic, specifically focusing on lives saved and the associated public health costs.MethodsThis retrospective cohort study was conducted April 6 to June 29. The 200-bed field hospital, a collaboration between Sociedade Beneficente Israelita Brasileira Albert Einstein and the São Paulo City Hall, São Paulo Municipal Health Departament, operated at Pacaembu Stadium and admitted. Adult patients with mild to moderate COVID-19. Electronic health records provided comprehensive data on demographics, clinical outcomes, and resource utilization. The mortality rate among field hospital patients was compared to that of two groups: I-confirmed COVID-19 cases in São Paulo, and II-severe acute respiratory syndrome patients with COVID-19 in São Paulo.ResultsA total of 152,928 COVID-19 cases were confirmed in São Paulo, with 20,603 patients hospitalized for ARDS and 1,499 patients admitted to the Pacaembu Field Hospital for mild to moderate disease. The median age of Pacaembu patients was 57 years (IQR 46–67), with 43.8% aged 60 or older. Lung disease was the most common comorbidity, affecting 31.0% of cases. The median length of stay was 4.2 days, and 14.2% of patients required intensive care, with 7.9% needing mechanical ventilation. The hospital had a survival rate of 99.8%. The cost per year of life saved, adjusted for gender, was R$44,243.02 (US$8,208.35). In the most favorable scenario, approximately 200 lives were saved, with a cost of R$5,640.92 (US$1,046.55) per life saved for both genders. In the least favorable scenario, around 50 lives were saved, with a cost of R$36,863.48 (US$6,839.24) per life saved for both genders, all within cost-effectiveness thresholds.ConclusionThe Pacaembu Field Hospital played a crucial role in saving lives during the initial COVID-19 wave, highlighting the importance of ongoing evaluation and resource optimization in field hospital strategies for an effective pandemic response.